G246(P) Opportunities and Challenges in Sustaining a Trainee Led Regional Mrcpch Clinical Revision Course. (24th May 2017) - Basu, S; Vasudevan, C; Newbegin, R; Dalton, L; McKeating, C; Williamson, V; Shaw, L
Abstract : We describe the experience and evaluation of a trainee led regional MRCPCH clinical course. Supporting trainees through the clinical exam has been a challenge for our local School of Paediatrics. A trainee led initiative has resulted in a successful two-day exam course which has made a significant impact on trainee confidence when approaching the exams. The course is held on a weekend and is delivered by experienced consultants, administrated by a local postgraduate education department and delivers clinical examination, communication, history taking and video teaching. There is also an OSCE circuit with real patients and top tips from senior trainees. The course is non-profit and charged at cost for the two days. Aims: To describe the experience of organising a two-day comprehensive MRCPCH clinical course over four years that has resulted from a trainee led initiative. Method: Structured qualitative feedback has been obtained from trainees who have attended the course over the past four years. Trainees filled in Pre-course questionnaires that explored their confidence level (scale of 1 5) in approaching individual stations and were evaluated after the course with a post course questionnaire. Feedback was also obtained about various other aspects of the course and their overall experience. The data was descriptively analysed and questionnaires were compared with identify any change in confidence. Results: 86 trainees have attended the course in the last four years. The course demonstrated improved confidence in approaching every clinical station but significant improvement was seen in the development station. The cost of the course, the authenticity and variety of clinical signs in patients, involvement of senior trainees and the quality of the faculty were identified as the major highlights. The course has evolved with changes incorporated from the feedback and continues to attract trainees. Conclusion: We feel significant improvements to trainee confidence in approaching the membership exam have been made. Senior trainee engagement has been a chief contributor to success and the course has provided a positive role model for other trainee led initiatives within the region.